Gaya Hidup yang Berpengaruh terhadap Kejadian Stroke Iskemik pada Usia Kurang dari 45 Tahun (Studi Pada BLUD RSUD Cut Nyak Dhien Meulaboh Kabupaten Aceh Barat Provinsi Aceh) - Arif Iskandar; Suharyo Hadisaputro; Dwi Pudjonarko; Suhartono Suhartono; Dodik Tugasworo Pramukarso (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background: Ischemic stroke that occurs at the age of less than 45 years accounts for about 5 until 10 percent of the total stroke. This is inﬂuenced by changes in the life-style of modern society, such as changes in the pattern of food consumption, lazy to move, and smoking habits. This study aims to examine the effect of life-style on ischemic stroke at less than 45 years old people.Method: This study uses observational method with design of cases and controls. The samples are 86 observations consisting of 43 cases and 43 controls. Cases are patients with ischemic stroke less than 45 years of age and controls are non-stroke patients of neurology who are less than 45 years old.Results: The results show that the habit of consuming food containing high fat (p=0,032, OR=3,744, 95% CI=1,124-12,468) and smoking habit (p=0,019, OR=3.859, 95% CI=1,250-11,911) affect the occurrence of ischemic stroke at age less than 45 years. However, the habit of consuming red meat, consuming foods containing high salt, consuming drugs, and lack of physical activity do not affect the occurrence of ischemic stroke at age less than 45 years.Conclusion: The habits of consuming food containing high fat and smoking affect theoccurrence of ischemic stroke at age less than 45 years after hypertension, heart disease, and diabetes mellitus are controlled.